Development of subjective well-being in adolescents before and during the COVID-19 pandemic - Eckert, Helene; Paschke, Patrick; Wirthwein, Linda; Steinmayr, Ricarda (Frontiers in Education, 2025)
Previous studies have already revealed detrimental effects of the COVID-19 pandemic on school students’ subjective well-being (SWB). However, there is a lack of studies examining the development of various facets of SWB such as life satisfaction, mood as well as domain satisfactions regarding peers, family, or school before and during the pandemic among adolescents longitudinally. Furthermore, the present study aims to shed further light on various moderators such as gender, age, migration background and socioeconomic status. Data from N = 207 students (Grade 5 to 9) from two German schools were assessed on four measurement time points, three before and one after the onset of the pandemic. Piecewise latent growth curve models with three time slopes were conducted to investigate the development of SWB and its moderators. They showed significant declines in general mood and domain-specific satisfaction with family, peers and school before the COVID-19 pandemic. However, during the COVID-19 pandemic, only satisfaction with family decreased significantly. Among the moderators, especially the socioeconomic status indicated interindividual differences in the variation of different SWB facets.